1991
DOI: 10.1007/bf00587615
|View full text |Cite
|
Sign up to set email alerts
|

Report from the International Pancreas Transplant Registry

Abstract: From December, 1966 through 1990, 3082 pancreas transplants were reported to the International Registry. A detailed analysis was performed on the 2087 transplants in the 1986-90 data base; during this time the overall one year recipient and graft functional survival rates were 89% and 62%. Univariate analyses showed graft survival rates to be significantly higher with bladder drainage than with other duct management techniques, with a simultaneous kidney transplant than without, and with preservation in UW tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…47 For cadaver solitary pancreas transplants, the rejection rate remained high with the immunosuppression available at the time (Minnesota antilymphocyte globulin, azathioprine, and prednisone). Although International Pancreas Transplant Registry data 42 showed that SPK transplants gave an advantage in terms of pancreas graft survival, we believed that the immunologic problems of solitary pancreas transplants could be overcome. We persisted with the philosophy that PTA was the most logical application: why wait for secondary complications?…”
Section: Eramentioning
confidence: 99%
See 1 more Smart Citation
“…47 For cadaver solitary pancreas transplants, the rejection rate remained high with the immunosuppression available at the time (Minnesota antilymphocyte globulin, azathioprine, and prednisone). Although International Pancreas Transplant Registry data 42 showed that SPK transplants gave an advantage in terms of pancreas graft survival, we believed that the immunologic problems of solitary pancreas transplants could be overcome. We persisted with the philosophy that PTA was the most logical application: why wait for secondary complications?…”
Section: Eramentioning
confidence: 99%
“…In contrast, every other program in the world performed only or predominately SPK transplants during this period. 42 Initially, we did not have a good marker to monitor for solitary pancreas graft rejection episodes, because an elevation in the plasma glucose level is a late manifestation (as opposed to elevation of the serum creatinine level in kidney graft recipients, which is a relatively early marker of renal allograft rejection, and one that gives an immunologic advantage to SPK recipients because serum creatinine can be used as a surrogate marker to detect rejection that usually affects both organs from the same donor). Duct management techniques later solved the problem, but initially we used other tactics.…”
mentioning
confidence: 99%
“…Improvements in surgical techniques and immunosuppressive drug regimens over the past 20 years have resulted in an increase in both patient and pancreas graft survival after transplantation as well as freedom from exogenous insulin administration in well over 80% of cases at 1 year posttransplantation in most centers (1,2). The surgical technique most commonly used in North America involves whole-organ transplantation with anastomosis of the duodenal segment to the bladder for drainage of the exocrine secretions and with systemic venous anastomosis to the iliac vein (KPT-S).…”
mentioning
confidence: 99%
“…Since the first human pancreatic transplantation (PTx) attempt by Kelly et al in 1966 [1], PTx has been applied with increasing frequency for the treatment of diabetes mellitus and has become the only accepted treatment which consistently establishes a normoglycemic, insulinindependent state [2][3][4]. Development in PTx depends on the understanding of the pathophysiologic alterations, improvement of surgical techniques, and development of more effective immunosuppressive agents, all of which are achievable by experimental research using animal models.…”
Section: Introductionmentioning
confidence: 99%